Pela melhoria do tratamento da insuficiência cardíaca em Portugal – documento de consenso - Fonseca, Cândida (2017)
Heart failure is a syndrome with high prevalence, morbidity and mortality, but awareness of the disease is poor among the general public and policy makers. This document, which was prepared by a group of experts consisting of cardiologists, internists and general practitioners, aims to set out in detail the problem of heart failure in Portugal at several levels: burden of the disease, diagnosis, treatment and monitoring. To this aim, different aspects of the management of the various stages of the disease are identified and discussed in detail, covering both outpatients and hospitalized patients. In order to optimize the medical care provided to these patients, various short‐, medium‐ and long‐term solutions and strategies are put forward that have the potential to improve the integration and use of available resources. The intention is to highlight strategies that are not based on a single model but can be adapted to different regional circumstances, in order to increase awareness and improve management of heart failure in Portugal.